2016
DOI: 10.1682/jrrd.2014.10.0252
|View full text |Cite
|
Sign up to set email alerts
|

Association between pain outcomes and race and opioid treatment: Retrospective cohort study of Veterans

Abstract: Abstract-We examined whether pain outcomes (pain interference, perceived pain treatment effectiveness) vary by race and then whether opioid use moderates these associations. These analyses are part of a retrospective cohort study among 3,505 black and 46,203 non-Hispanic, white Department of Veterans Affairs (VA) patients with diagnoses of chronic musculoskeletal pain who responded to the 2007 VA Survey of Healthcare Experiences of Patients (SHEP). We used electronic medical record data to identify prescriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Beyond pharmaceutical treatments, several studies have examined racial and ethnic differences in multidisciplinary pain treatment program outcomes. In a large retrospective study performed at the Department of Veterans Affairs, Burgess and colleagues found no significant association between race and pain outcomes for a multidisciplinary pain treatment program [181]. However, in Merry and colleagues study examining race differences in pain-related treatment outcomes, both black and white participants experienced a reduction in pain-related interference, but only white participants reported reduced pain severity [182].…”
Section: Racial and Ethnic Differences In Pain Treatment Outcomesmentioning
confidence: 99%
“…Beyond pharmaceutical treatments, several studies have examined racial and ethnic differences in multidisciplinary pain treatment program outcomes. In a large retrospective study performed at the Department of Veterans Affairs, Burgess and colleagues found no significant association between race and pain outcomes for a multidisciplinary pain treatment program [181]. However, in Merry and colleagues study examining race differences in pain-related treatment outcomes, both black and white participants experienced a reduction in pain-related interference, but only white participants reported reduced pain severity [182].…”
Section: Racial and Ethnic Differences In Pain Treatment Outcomesmentioning
confidence: 99%
“…Yazdanshenas, Bazargan, and colleagues (2016) revealed that there is severe mismanagement of pain among African-American older adults, which may be attributed to potentially inappropriate medications, such as opioids [ 47 ]. Further, Burgess and colleagues (2016) found opioid users reported greater pain interference compared to non-opioid users [ 48 ]. Even though African-Americans are undertreated with opioid-based medications, they are at higher odds for opioid abuse and dependence as opposed to Whites [ 49 ].…”
Section: Discussionmentioning
confidence: 99%